Lingkungan Pengendapan Perairan Selatan Estuaria Bagan dan Sekitarnya Pantai Timur Sumatera Indonesia - Rifardi Rifardi; Edwar Rufli; Andre Rangga; M Lubis; Yenica Roza; Putri Nilam Sari (Jurnal Ilmu Lingkungan, 2011)
The main purpose of this study is to clarify the relation between characteristics of sediments andenvironmental condition based on the analysis of surface sediment samples and total suspendedsediments from the Southern of Bagan Estuary which is located on the East Coast of SumateraIsland, Indonesia. Surface sediment samples and total suspended sediments were collected at 21stations using sediment sampler and van dorm sampler, respectively, in June 2010. The sampleswere analyzed by various analytical approaches i.e. mechanical grain size analysis, ignitionloss method, bulk chemical analysis using atomic absorption spectrometer and sand-graincomposition analysis. In general, the estuary area is characterized by finer sediments (medium-grained sand), by the lower values of organic matters (less than10%), and by the higher contentof Fe and Al per non calcareous clastic content, which is an index of terrigenous material inputrespectively. Concentration of total suspended sediment near bottom is higher than that ofsurface water, indicating sediments turbulented by strong current system. Judging from thedistribution pattern of the Fe and K contents at surface sediment, terrigenous materials weretransported northwestward along the coast of Pekaitan Village and of Barkey Island by strongebb current. Contrastingly, terrigenous materials were transported southeastward along thearea located between coast of Pekaitan Village and of Barkey Island by strong tide current.Geographical distribution of sand grain composition (lithogenous) strongly indicate thatterrigenous materials derived from the hinterland of Sumatera Island discharged through RokanRiver to the Southern of Bagan Estuary. In addition to, terrigenous materials are also resultedfrom coast erosion of Pekaitan Village and of Barkey Island, and turbulented sediments.